Cathode material for lithium-sulfur batteries and lithium-sulfur batteries including the same
By using sulfur-doped pore carbon material and transition metal catalyst carbon composite as the positive electrode material of lithium-sulfur battery, the problem of low conductivity of the positive electrode material of lithium-sulfur battery is solved, and higher kinetic performance and cycle life are achieved.
Patent Information
- Application Number
- JP2023545356
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-10-27
- Filing Date
- 2022-12-16
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-12-16
AI Technical Summary
The existing positive electrode materials for lithium sulfur batteries have low conductivity during charging and discharging, resulting in insufficient adsorption and release of lithium polysulfides, affecting the dynamic performance and life of the battery.
A carbon composite is used as the positive electrode material, which consists of sulfur-doped porous carbon material and a catalyst containing transition metal. The nearest distance between the transition metal and the porous carbon material is controlled within 10 nanometers, which improves the surface characteristics and catalytic activity of the material.
It improves the kinetic performance of lithium-sulfur batteries during charging and discharging, enhances the adsorption ability of the positive electrode to lithium polysulfide, extends the cycle life of the battery and increases the energy density.
Smart Images

Figure 0007667290000002 
Figure 0007667290000003 
Figure 0007667290000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode material for a lithium-sulfur battery and a lithium-sulfur battery including the same.
[0002] This application claims priority to Korean Application No. 2022-0044174 filed on April 8, 2022 and Korean Application No. 2022-0140744 filed on October 27, 2022, the entire contents of which are incorporated herein by reference in their entirety. [Background technology]
[0003] Lithium-sulfur batteries are battery systems that use sulfur-based materials with sulfur-sulfur bonds as the positive electrode active material and lithium metal as the negative electrode active material. Sulfur, the main material of the positive electrode active material, is a globally abundant resource and has the advantages of being non-toxic and having a low weight per atom.
[0004] As the application areas of secondary batteries expand to electric vehicles (EVs) and energy storage systems (ESS), lithium-sulfur battery technology is attracting attention because it can theoretically achieve a high energy storage density (up to 2,600Wh / kg) relative to its weight, compared to lithium-ion secondary batteries, which have a relatively low energy storage density (up to 250Wh / kg) relative to their weight.
[0005] During discharge, lithium, the negative electrode active material, is oxidized as it releases electrons and is ionized into lithium cations, while the positive electrode active material, the sulfur-based material, is reduced as it accepts electrons. Here, the S-S bond accepts two electrons and is converted into a sulfur anion form through the reduction reaction of the sulfur-based material. The lithium cations generated by the oxidation reaction of lithium are transferred to the positive electrode through the electrolyte, and combine with the sulfur anions generated through the reduction reaction of the sulfur-based compound to form a salt. Specifically, sulfur before discharge has a cyclic S8 structure, which is reduced to lithium polysulfide (Li2S) through a reduction reaction. x ) which is then completely reduced to produce lithium sulfide (LiS).
[0006] As sulfur used as the positive electrode active material is a non-conductor, it is difficult for electrons generated in the electrochemical reaction to move, and polysulfides (LiS x ) leaching problem and the slow kinetic activity of electrochemical reactions due to the low electrical conductivity of sulfur and lithium sulfide, resulting in reduced battery life and rate characteristics.
[0007] In relation to this, research is being conducted to improve the performance of lithium-sulfur secondary batteries by using platinum (Pt), which is widely used recently as an electrochemical catalyst, to improve the kinetic activity of the sulfur redox reaction during the charge and discharge process of the lithium-sulfur secondary battery. However, precious metal catalysts such as platinum are expensive and therefore difficult to commercialize, and there is also a problem that they can be poisoned by the sulfur redox reaction during the charge and discharge process, making it difficult to use them as positive electrode materials for lithium-sulfur secondary batteries.
[0008] In addition, research is being conducted on single atomic catalyst materials to improve the performance of lithium-sulfur secondary batteries by minimizing the catalyst content inside the positive electrode by increasing the atomic utilization efficiency to a level close to 100%. However, most single atomic catalysts have a low adsorption rate with lithium sulfide, which results in low conversion performance, so the current situation is that they are still insufficient in improving the performance of lithium-sulfur secondary batteries. As a result, research has been conducted on using single atomic catalysts together with particle type catalysts, but in that case, the atomic utilization efficiency is again reduced, so there is still a problem that it is not effective.
[0009] Therefore, there is a continuing need for technological development of positive electrode materials that can improve the kinetic activity of the electrochemical reactions during charging and discharging of lithium-sulfur secondary batteries and at the same time are cost-effective and advantageous for commercialization. Summary of the Invention [Problem to be solved by the invention]
[0010] Therefore, the problem to be solved by the present invention is to provide a cathode material that solves the above-mentioned problems, has excellent adsorption power with lithium polysulfide, and enhances the kinetic activity of sulfur oxidation / reduction reaction.
[0011] This provides a high-performance lithium-sulfur secondary battery. [Means for solving the problem]
[0012] In order to solve the above problems, according to one aspect of the present invention, there is provided a carbon composite having the following configuration.
[0013] The carbon composite according to the first aspect comprises: at least one sulfur-doped porous carbon material; and at least one catalyst comprising one or more transition metals, the catalyst located on at least one of an exterior surface and interior surfaces of the pores of the at least one sulfur-doped porous carbon material.
[0014] According to the second aspect, in the first aspect, The nearest neighbor interatomic distance between the transition metal contained in the catalyst and the at least one sulfur atom doped in the porous carbon material may be 10 nm or less.
[0015] According to the third aspect, in the first or second aspect, The nearest neighbor interatomic distance between the transition metal contained in the catalyst and the at least one sulfur atom doped in the porous carbon material may be 2 nm or less.
[0016] According to the fourth aspect, in any one of the first to third aspects, The carbon composite is 200 m 2 / g or more.
[0017] According to the fifth aspect, in any one of the first to fourth aspects, The catalyst may further comprise the transition metal and at least one non-metallic element that forms a ligand with the transition metal.
[0018] According to the sixth aspect, in any one of the first to fifth aspects, The catalyst may further comprise the transition metal, at least one non-metallic element that forms a ligand with the transition metal, and an organic support.
[0019] According to the seventh aspect, in any one of the first to sixth aspects, The catalyst may include a single atom catalyst containing one or more transition metals, and the one or more transition metals may have a morphology in which the size of a single atom is dispersed within the carbon composite.
[0020] According to the eighth aspect, in any one of the first to seventh aspects, The catalyst may not contain metallic bonds between two or more transition metals.
[0021] According to the ninth aspect, in any one of the first to eighth aspects, The catalyst comprises particles comprising one or more transition metals, the particles having an average diameter (D 50 ) may be from 1 to 30 nm, the diameter of a single atom constituting the transition metal.
[0022] According to a tenth aspect, in any one of the first to ninth aspects, The catalyst comprises particles comprising one or more transition metals, the particles having an average diameter (D 50 ) may be 1 to 5 times the diameter of a single atom constituting the transition metal.
[0023] According to an eleventh aspect, in any one of the first to tenth aspects, The transition metal may include zinc (Zn), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zirconium (Zr), niobium (Nb), molybdenum (Mo), technetium (Tc), rubidium (Ru), rhodium (Rh), palladium (Pd), silver (Ag), cadmium (Cd), lanthanum (La), hafnium (Hf), tantalum (Ta), tungsten (W), osmium (Os), iridium (Ir), cerium (Ce), gallium (Gd), scandium (Sc), titanium (Ti), gallium (Ga), indium (In), or two or more thereof.
[0024] According to the 12th aspect, in any one of the 1st to 11th aspects, The transition metal may include iron (Fe).
[0025] According to a thirteenth aspect, in any one of the first to twelfth aspects, The transition metal contains iron (Fe), and the diameter (D 50 ) may be 0.3 nm to 5 nm.
[0026] According to a 14th aspect, in any one of the 1st to 13th aspects, The molar ratio of the sulfur doped in the porous carbon material to the one or more transition metals contained in the catalyst may be 0.5-8.
[0027] According to a fifteenth aspect, in any one of the first to fourteenth aspects, The at least one sulfur may be doped in the form of sulfur atoms or sulfur compounds.
[0028] According to a 16th aspect, in any one of the 1st to 15th aspects, The at least one sulfur-doped porous carbon material includes at least one of a first structure according to the following formula 1 and a second structure according to the following formula 2, and the ratio of the first structure to the second structure, which is a molar ratio of the first structure / the second structure, may be 1 or less.
[0029] [Formula 1] -C-SO2-C- [Formula 2] -CSC-
[0030] According to the seventeenth aspect, in the sixteenth aspect, The molar ratio of the first structure / second structure may be 0.1 to 0.7.
[0031] According to an 18th aspect, in any one of the 1st to 17th aspects, When the number of pores having a pore diameter of less than 10 nm among all pores in the carbon composite is defined as N(nano) and the number of pores having a pore diameter of 10 nm or more is defined as N(macro), the ratio of N(macro) to N(nano) [N(macro) / N(nano)] may be 1 or more.
[0032] According to the 19th aspect, in any one of the 1st to 18th aspects, The Raman peak intensity ratio (I G / I D The ratio may be less than or equal to 1.
[0033] According to another aspect of the present invention, there is provided a method for producing a carbon composite having the following features.
[0034] A method for producing a carbon composite according to a twentieth embodiment includes the steps of: The method includes: (S1) doping at least one sulfur atom in a porous carbon material; and (S2) impregnating the result of step (S1) with a transition metal-containing precursor solution and then removing the solvent, wherein step (S1) includes a heat treatment step in which the sulfur-doped precursor and the porous carbon material are in contact with each other.
[0035] According to the twenty-first aspect, in the twenty-first aspect, The heat treatment may be carried out at a temperature of 800°C to 1,000°C.
[0036] According to the 22nd aspect, in the 20th or 21st aspect, The sulfur-doped precursors include dibenzyl disulfide (DBDS), sodium metabisulfite (Na2S2O5), sodium pyrosulfate (Na2S2O7), sodium thiosulfate (Na2S2O3), thiourea (CH4N2S), sodium sulfide (Na2S), potassium thiocyanate (KSCN), benzyl mercaptan (C7H8S), benzothiophene (C8H6S), dibenzothiophene (C1H1S), and benzothiophene (C1H1S). 12 H8S, dibenzohiophene, or mixtures thereof.
[0037] According to the 23rd aspect, in any one of the 20th to 22nd aspects, The transition metal-containing precursor solution in the step (S2) may include an organic solvent, a precursor compound of a nonmetal element, and a precursor compound of a transition metal.
[0038] According to still another aspect of the present invention, there are provided a positive electrode active material, a positive electrode, a lithium-sulfur battery, and a battery having the following embodiments.
[0039] According to a twenty-fourth aspect, There is provided a positive electrode active material including the carbon composite according to any one of the first to nineteenth aspects and a sulfur-based compound.
[0040] According to the twenty-fifth aspect, A positive electrode is provided that includes the positive electrode active material according to the twenty-fourth embodiment.
[0041] According to the twenty-sixth aspect, There is provided a lithium-sulfur battery comprising a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, wherein the positive electrode is the positive electrode according to the twenty-fifth embodiment.
[0042] According to the twenty-seventh aspect, There is provided a positive electrode comprising a positive electrode active material containing a sulfur-based compound and the carbon composite according to any one of the first to nineteenth aspects.
[0043] According to the twenty-eighth aspect, There is provided a lithium-sulfur battery comprising a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, wherein the positive electrode is the positive electrode according to the twenty-seventh embodiment.
[0044] According to the twenty-ninth aspect, There is provided a battery including a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, wherein at least one of the positive electrode and the negative electrode includes the carbon composite according to any one of the first to nineteenth aspects. Effect of the Invention
[0045] The carbon composite according to one embodiment of the present invention is a lithium polysulfide (LiPS, LiS x , 2≦x≦8). In addition, the carbon composite has advantageous properties for ion transport and electron transport, which are essential for the conversion reaction of lithium polysulfide.
[0046] In addition, the carbon composite has the effect of providing excellent kinetic activity in the oxidation / reduction reaction of sulfur.
[0047] Furthermore, the carbon composite has the effect of improving the atom utilization rate as a catalyst.
[0048] As a result, a lithium-sulfur secondary battery using the carbon composite as a support for a positive electrode additive and / or a positive electrode active material has the effect of suppressing the elution of lithium polysulfide into the electrolyte and improving the conversion rate of sulfur, thereby achieving stable high performance.
[0049] In particular, the lithium-sulfur battery according to an embodiment of the present invention has excellent effects in terms of initial capacity, capacity retention rate through charge / discharge cycles, and battery energy density.
[0050] The drawings attached to this specification are intended to illustrate preferred embodiments of the present invention and serve to facilitate a further understanding of the technical ideas of the present invention as well as the content of the invention, and therefore the present invention should not be interpreted as being limited to only the matters depicted in the drawings. [Brief description of the drawings]
[0051] [Figure 1] FIG. 1 is a schematic diagram of various functions showing that a carbon composite according to one embodiment of the present invention functions as an electrochemical catalyst in a positive electrode during charging and discharging of a lithium-sulfur secondary battery. [Figure 2a] FIG. 1 is a schematic diagram of a manufacturing sequence of a carbon composite and a positive electrode using the same according to one embodiment of the present invention. [Figure 2b]1 is a graph showing the results of a 2p spectrum of a sulfur atom (S) in the carbon composite of Example 1 of the present specification, obtained by XPS analysis. [Figure 2c] 1 is a graph showing the results of a 2p spectrum of a sulfur atom (S) in a carbon composite of Example 2 of the present specification, obtained by XPS analysis. [Figure 2d] 1 is a graph showing the measurement results of the Fe element content and the -SO2 / -S ratio in Comparative Example 1 (FeNC), Example 1 (FeNC-EEB-1), and Example 2 (FeNC-EEB-2) of the present specification, obtained by ICP-AES analysis. [Diagram 3] 1 is an image showing the analysis results of the distribution of Fe, O, N, C, and S in Example 1 (FeNC-EEB-1) and Example 2 (FeNC-EEB-2) of the present specification obtained by EDS analysis. [Figure 4] 1 shows images obtained by SEM (left) and TEM (right) showing the morphology of Comparative Example 1 (FeNC), Example 1 (FeNC-EEB-1), and Example 2 (FeNC-EEB-2) herein. [Diagram 5] FIG. 1 is a graph showing pore diameter and relative pressure results obtained by nitrogen physisorption analysis for Comparative Example 1 (FeNC), Example 1 (FeNC-EEB-1), and Example 2 (FeNC-EEB-2) herein. [Figure 6] 1 shows images obtained by STEM showing the shapes of Comparative Example 1 (FeNC), Example 1 (FeNC-EEB-1), and Example 2 (FeNC-EEB-2) of the present specification. [Figure 7] FIG. 1 is a graph showing the results obtained by FT-EXAFS to confirm the bonding of Fe elements in Comparative Example 1 (FeNC), Example 1 (FeNC-EEB-1), Example 2 (FeNC-EEB-2), and Fe foil of the present specification. [Figure 8] 1 is a graph showing the results of Fe K-edge XANES measurement of Comparative Example 1 (FeNC), Example 1 (FeNC-EEB-1), and Example 2 (FeNC-EEB-2) of the present specification. [Figure 9a]FIG. 1 is a graph of Tafel plots obtained by measuring the current / voltage of the cathode and the anode during operation of the lithium-sulfur coin batteries of Comparative Example 2 (FeNC), Example 3 (FeNC-EEB-1), and Example 4 (FeNC-EEB-2) of the present specification. [Figure 9b] 1 is a graph showing the results of constant voltage (2.05 V) discharge drive of Comparative Example 2 (FeNC), Example 3 (FeNC-EEB-1), and Example 4 (FeNC-EEB-2) of the present specification. [Figure 9c] 1 is a graph showing the results of constant voltage (2.35 V) charge driving of Comparative Example 2 (FeNC), Example 3 (FeNC-EEB-1), and Example 4 (FeNC-EEB-2) of the present specification. [Figure 10] 1 is a graph showing the evaluation results of the charge-discharge performance of Comparative Example 2 (FeNC), Example 3 (FeNC-EEB-1), and Example 4 (FeNC-EEB-2) of the present specification. [Figure 11] 1 is a graph showing the results of evaluating 200 charge / discharge cycles of Comparative Example 2 (FeNC), Example 3 (FeNC-EEB-1), and Example 4 (FeNC-EEB-2) of the present specification. [Figure 12] FIG. 13 is a graph showing the results of evaluating 100 charge / discharge cycles after changing the sulfur loading amount and E / S ratio in Example 3 (FeNC-EEB-1) of the present specification. [Figure 13] 1 is a graph showing the results of evaluating the charge / discharge performance of Comparative Example 3 and Example 5 of the present specification. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0052] The present invention will be described in detail below. However, the present invention is not limited to the following content, and each component may be modified or mixed selectively as necessary. Therefore, it is understood that the present invention includes all modifications, equivalents, and alternatives within the spirit and technical scope of the present invention.
[0053] In this specification, when a certain configuration "comprises" a certain component, this does not mean that other components are excluded, but that other components may be further included, unless otherwise specified.
[0054] In this specification, the phrase "A and / or B" means "A or B or both."
[0055] Certain terminology used herein is for convenience and not limitation. For example, positional terms such as "upper," "lower," "left," "right," "front," "rear," "inner," and "outer" are not intended to denote absolute positions, but are used to indicate relative positions and orientations of components relative to one another or in the drawings to which reference is made. The terms used herein include, in addition to themselves, words containing these terms, their derivatives, and words of similar meaning.
[0056] According to one aspect of the present invention, there is provided a carbon composite that can be utilized as an electrochemical catalyst in the positive electrode of a lithium-sulfur secondary battery.
[0057] FIG. 1 illustrates various functions of the carbon composite according to the present invention functioning as an electrochemical catalyst in the positive electrode during charging and discharging of a lithium-sulfur secondary battery. Referring to FIG. 1, the carbon composite is used as an electrochemical catalyst in the positive electrode, and thus lithium polysulfide (Li2S x or LiS x - , x = 8, 6, 4, 2) and can suppress dissolution into the electrolyte. It also shows activity in the conversion reaction between lithium polysulfides, inducing rapid conversion and preventing the release of lithium sulfide (Li2S).
[0058] A carbon composite according to one aspect of the present invention comprises at least one sulfur-doped porous carbon material and at least one catalyst comprising one or more transition metals, the catalyst being located on at least one of an exterior surface and interior surfaces of pores of the sulfur-doped porous carbon material.
[0059] In one embodiment of the present invention, the transition metal-containing catalyst may be chemically and / or physically bound to at least one of the exterior surface and the interior surfaces of the pores of the sulfur-doped porous carbon material.
[0060] In one embodiment of the invention, the catalyst may be physically adsorbed on the external surface and / or the internal surfaces of the pores of the porous carbon material and / or chemically bonded by covalent bonds between elements contained in the catalyst and carbon of the porous carbon material.
[0061] In the carbon composite of the present invention, at least one sulfur atom is present at a position adjacent to a catalyst present on the outer surface and / or inside the pores of the porous carbon material. In this specification, the "adjacent" position means a position where the nearest atomic distance between the catalyst and the at least one sulfur atom doped in the porous carbon material is 10 nm or less.
[0062] In this specification, the nearest interatomic distance refers to the center-to-center distance between two atoms that are closest to each other. The nearest interatomic distance can represent a value measured according to a known method for measuring interatomic distances, and is not particularly limited to a measurement method. For example, the nearest interatomic distance can be measured using a transmission electron microscope (TEM), an atomic force microscope (AFM), a field-emission electron microscope (FE-SEM), or a laser diffraction method.
[0063] In one embodiment of the present invention, the nearest neighbor atomic distance between the catalyst and the at least one sulfur doped in the porous carbon material may be 10 nm or less, specifically 5 nm or less, more specifically 2 nm or less, such as 1.5 nm or less or 1 nm or less.
[0064] For example, the nearest neighbor atomic distance between the catalyst and at least one sulfur atom doped in the porous carbon material can represent the nearest neighbor atomic distance between a transition metal element contained in the catalyst and at least one sulfur atom doped in the porous carbon material.
[0065] In the carbon composite, the sulfur-doped position can act as an electron exchangeable binding (EEB) site. In addition, the sulfur can adjust the orbital level of the transition metal via electron exchange with the transition metal in the catalyst. For example, when the catalyst contains iron (Fe) as a transition metal, the sulfur can adjust the d-orbital level of iron via electron exchange with iron (Fe). As a result, the carbon composite can promote the kinetic activity for the reduction reaction of lithium polysulfide, but the mechanism of the present invention is not limited thereto.
[0066] In the present invention, the catalyst containing the transition metal can be used alone as a catalyst in the positive electrode of a lithium-sulfur battery to activate the reduction reaction of lithium polysulfide. However, according to the present invention, the catalyst is located on the outer surface and / or the inner surface of the pores of the at least one sulfur-doped porous carbon material, which can further improve the adsorption of lithium polysulfide and the activation of the oxidation / reduction reaction of sulfur.
[0067] In one embodiment of the present invention, the catalyst includes a transition metal as an active component of the catalyst, and may include, without limitation, any transition metal that can mediate the oxidation / reduction reaction of sulfur.
[0068] In another embodiment of the present invention, the catalyst may further comprise the transition metal and at least one non-metallic element forming a ligand with the transition metal, wherein the transition metal and / or the non-metallic element present in the catalyst may be physically adsorbed and / or chemically bonded to the carbon of the porous carbon material.
[0069] In yet another embodiment of the present invention, the catalyst may further include the transition metal, at least one nonmetallic element forming a ligand with the transition metal, and an organic support. When the catalyst further includes an organic support for supporting the transition metal and the nonmetallic element, the dispersibility of the transition metal can be improved, thereby improving the catalyst utilization rate of the carbon composite according to one aspect of the present invention.
[0070] In yet another embodiment of the invention, the catalyst comprises an organic support, a transition metal, and at least one non-metallic element that forms a ligand with the transition metal, and the catalyst may comprise a bond between carbon in the organic support and the transition metal, a bond between the carbon and the non-metallic element, and a bond between the transition metal and the non-metallic element.
[0071] In one embodiment of the present invention, the catalyst may contain a transition metal in the form of metal particles formed by bonds between the transition metal atoms. However, from the viewpoint of the atomic utilization rate of the catalyst, it is preferable that the catalyst contains a transition metal that exists as a single atom without being bonded between transition metal atoms.
[0072] Thus, according to one aspect of the present invention, the catalyst may include a single-atom catalyst containing one or more transition metals, whereby the one or more transition metals contained in the catalyst may have a form in which they are dispersed in the carbon composite at a single atomic size.
[0073] In the present specification, the term "single atom catalyst (SAC)" refers to a catalyst in which a catalytically active site is expressed in atomic units, and the carbon composite may include a single atom catalyst containing a transition metal as a catalyst.
[0074] According to one aspect of the present invention, the catalyst may not include metallic bonds between transition metals in the structure. That is, the catalyst may not include metal particles formed through metallic bonds between two or more transition metal atoms in the structure. Specifically, the carbon composite according to one aspect of the present invention does not include metallic bonds between two or more transition metals contained in the catalyst.
[0075] In one embodiment of the present invention, the transition metal being contained in the porous carbon material and / or the organic support in a form dispersed at a single atomic size can be confirmed, for example, by observing the carbon composite and / or catalyst with a microscope such as a scanning electron microscope (SEM), a transmission electron microscope (TEM), or a scanning transmission electron microscope (STEM).
[0076] In another embodiment of the present invention, the catalyst contained in the carbon composite may include particles containing one or more transition metals, and the average diameter (D 50 ) may be, for example, 1 to 30 nm larger than the diameter of a single atom constituting the transition metal. 50 ) may have a diameter 1 to 5 times the diameter of a single atom constituting the transition metal. Preferably, the average diameter (D 50 ) may be 1 to 3 times the diameter of a single atom constituting the transition metal, and more preferably 1 time the diameter of a single atom constituting the transition metal. In other words, the catalyst most preferably has a morphology in which the transition metal is dispersed in the carbon composite at the size of a single atom.
[0077] In one embodiment of the present invention, the absence of metallic bonds between two or more transition metals in the catalyst can be confirmed, for example, by X-ray diffraction (XRD) analysis of the carbon composite and / or the catalyst.
[0078] In one embodiment of the present invention, the transition metal contained in the catalyst is not particularly limited as long as it can exhibit activity in the oxidation / reduction reaction of sulfur in the positive electrode of a lithium-sulfur battery. For example, the transition metal may be zinc (Zn), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zirconium (Zr), niobium (Nb), molybdenum (Mo), technetium (Tc), rubidium (Ru), rhodium (Rh), palladium (Pd), silver (Ag), cadmium (Cd), lanthanum (La), hafnium (Hf), tantalum (Ta), tungsten (W), osmium (Os), iridium (Ir), cerium (Ce), gallium (Gd), scandium (Sc), titanium (Ti), gallium (Ga), indium (In), or two or more of these.
[0079] In another embodiment of the present invention, the transition metal contained in the catalyst may be iron (Fe).
[0080] In one embodiment of the present invention, the diameter of a known iron (Fe) atom is 300 pm, and when the catalyst contained in the carbon composite of the present invention contains iron (Fe), the transition metal present in the carbon composite has a diameter (D 50 For example, it can be confirmed that the diameter (D 50 ) may be 0.5 nm to 2 nm, 0.3 nm to 1.5 nm, 0.3 nm to 1 nm, or 0.3 nm to 0.5 nm.
[0081] In one embodiment of the present invention, the nonmetallic element that forms a ligand with the transition metal in the catalyst may be appropriately selected depending on the type of the transition metal, and is not particularly limited.
[0082] In another embodiment of the invention, the non-metallic element forming a ligand with the transition metal in the catalyst can be, for example, hydrogen (H), boron (B), nitrogen (N), oxygen (O), fluorine (F), neon (Ne), silicon (Si), phosphorus (P), chlorine (Cl), bromine (Br), iodine (I), or two or more of these.
[0083] In yet another embodiment of the present invention, when the catalyst contains iron (Fe) as a transition metal, the catalyst may contain nitrogen (N) as the nonmetallic element. The catalyst may advantageously exhibit excellent catalytic activity when the iron forms a ligand with nitrogen, but the present invention is not limited thereto.
[0084] In one embodiment of the present invention, when the catalyst contains iron (Fe) as a transition metal and nitrogen (N) as a nonmetallic element, the catalyst may contain a structure in which one iron (Fe) atom is bonded to four nitrogen (N) atoms adjacent to the iron atom. When the catalyst contains a structure in which one iron atom is bonded to four nitrogen atoms adjacent to the iron atom, an advantageous effect can be obtained in terms of the activity stability of the carbon composite, but the present invention is not limited thereto.
[0085] As described above, since the catalyst is located on the outer surface and / or the inner surface of the pores of at least one sulfur-doped carbon material, the carbon composite according to the present invention can improve the catalytic activity in sulfur oxidation / reduction reactions.
[0086] In one embodiment of the present invention, the at least one sulfur-doped porous carbon material may be a porous carbon material prepared by carbonizing various carbon material precursors and doped with at least one sulfur.
[0087] The porous carbon material produced by carbonizing the precursors of the various carbon materials is not particularly limited as long as it is a material commonly used in the art. For example, the porous carbon material may be graphite, graphene, reduced graphene oxide (rGO), carbon black such as denka black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon nanotubes (CNT) such as single-walled carbon nanotubes (SWCNT) and multi-walled carbon nanotubes (MWCNT), carbon fibers such as graphite nanofibers (GNF), carbon nanofibers (CNF), and activated carbon fibers (ACF), graphite and activated carbon such as natural graphite, artificial graphite, and expanded graphite, fullerene, or activated carbon obtained by activating a carbon material.
[0088] According to the present invention, the carbon composite has a structure in which the porous carbon material as described above is doped with at least one sulfur.
[0089] In the present invention, the at least one sulfur-doped porous carbon material refers to a porous carbon material having a structure in which at least one carbon atom (C) of the porous carbon material is substituted with sulfur.
[0090] In one embodiment of the present invention, the content of sulfur doped into the porous carbon material may be, for example, a content such that the molar ratio of the sulfur doped into the porous carbon material to the one or more transition metals contained in the catalyst is 0.5 to 8. Specifically, the molar ratio of the sulfur doped into the porous carbon material to the one or more transition metals contained in the catalyst may be 0.5 to 5 or 1 to 3. When the molar ratio of the transition metal to sulfur is in the above range, an advantageous effect can be exhibited in terms of catalytic activity, but the present invention is not limited thereto.
[0091] The molar ratio of sulfur doped in the porous carbon material to the transition metal in the catalyst may be measured, for example, by inductively coupled plasma mass spectrometry (ICP-MS). When the content of the doped sulfur is small, it may be advantageous to use a high-resolution device for measurement accuracy, but the present invention is not limited thereto.
[0092] In one embodiment of the present invention, the at least one sulfur may be doped in the form of sulfur atoms or sulfur compounds.
[0093] Specifically, the sulfur doped in the form of a sulfur atom means that the structure of the porous carbon material contains a -CSC- structure in which a carbon atom is substituted with a sulfur atom, and the sulfur doped in the form of a sulfur compound means that the structure of the porous carbon material contains a -C-SY-C- structure in which a carbon atom is substituted with a sulfur compound (wherein SY represents a sulfur compound).
[0094] In one embodiment of the present invention, the form of the sulfur compound is, for example, sulfur oxide (SO x , 0.1≦x≦4).
[0095] In one embodiment of the present invention, the at least one sulfur-doped porous carbon material may include a structure in which sulfur is doped in the form of sulfur dioxide (SO2). Specifically, the sulfur-doped porous carbon material may include a -C-SO2-C- structure in its structure.
[0096] In one embodiment of the present invention, the at least one sulfur-doped porous carbon material may comprise within its structure a first structure according to Formula 1 below and / or a second structure according to Formula 2 below:
[0097] [Formula 1] -C-SO2-C- [Formula 2] -CSC-
[0098] In one embodiment of the invention, the at least one sulfur in the carbon composite can tune the orbital levels of a transition metal present in the catalyst, e.g., can transfer electrons between the sulfur doped site (i.e., EEB site) and a transition metal.
[0099] In this case, the order of the orbital levels of the transition metal and the EEB site is determined according to the type of transition metal, and the transition metal may function as an electron donor and the EEB site may function as an electron acceptor, or the transition metal may function as an electron acceptor and the EEB site may function as an electron donor.
[0100] In one embodiment of the present invention, the carbon composite may contain iron (Fe) as a transition metal in the catalyst, and the first and second structures may be contained in the structure of the at least one sulfur-doped porous carbon material. In this case, the role of the transition metal and the electron donor and / or electron acceptor of the EEB site may be determined depending on the ratio of the first structure to the second structure (first structure / second structure) at the position capable of forming a coordinate bond with the transition metal in the one catalyst.
[0101] In one embodiment of the present invention, the relationship between the transition metal and the electron donor / acceptor of the EEB site can be confirmed by measuring their orbital levels, but the mechanism of the present invention is not limited thereto.
[0102] For example, if the orbital level of the transition metal that exhibits catalytic activity in the carbon composite is low, electrons transfer from the transition metal to the EEB site, or if the orbital level of the transition metal is high, electrons transfer from the EEB site to the transition metal.
[0103] In one embodiment of the present invention, when the ratio of the first structure / second structure is high, the d-orbital level of iron (Fe) is lowered due to stabilization of the d-orbital of iron (Fe) by -SO2, and this can have activity in transferring electrons from iron to the EEB site.
[0104] In another embodiment of the present invention, when the ratio of the first structure / second structure is low, the stabilizing effect is reduced and the d-orbital (orbital) level of iron is elevated, which may have activity in transferring electrons from the EEB site to iron.
[0105] In this specification, the ratio of the first structure / second structure can indicate, for example, a molar ratio.
[0106] Thus, in one embodiment of the present invention, when the transition metal in the catalyst of the carbon composite contains iron (Fe), the catalytic activity can be further improved by electrons moving from the EEB site to the iron (Fe), so that the ratio of the first structure and the second structure (ratio of the first structure / second structure) in the structure of the at least one sulfur-doped porous carbon material may preferably be 1 or less. The ratio of the first structure and the second structure (ratio of the first structure / second structure) may be, for example, 1 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, 0.3 or less, 0.2 or less, or 0.15 or less. In addition, the ratio of the first structure / second structure may be 0.01 or more, 0.05 or more, or 0.1 or more. For example, the ratio of the first structure / second structure may be 0.01 or more and 1 or less, 0.05 or more and 0.8 or less, 0.10 or more and 0.7 or less, 0.10 or more and 0.5 or less, or 0.10 or more and 0.2 or less, but the present invention is not limited thereto.
[0107] When the carbon composite according to one aspect of the present invention is used in a positive electrode, it contains a large number of micropores for supporting a positive electrode active material and / or a catalyst within the carbon composite.
[0108] In one embodiment of the present invention, the carbon composite contains a large number of micropores on the outer surface and inside, and the micropores can be classified into nanopores having a diameter of less than 10 nm and macropores having a diameter of 10 nm or more depending on their size.
[0109] In one embodiment of the present invention, the diameter of the nanopores is less than 10 nm, specifically, 1 to 9.5 nm, 2 to 9 nm, 3 to 8 nm, 3.5 to 7 nm, 4 to 6 nm, 4 to 5 nm, or 4.0 to 4.5 nm.
[0110] In another embodiment of the present invention, the diameter of the macropores is 10 nm or more, specifically, 10 nm or more and 50 nm or less, 40 nm or less, 30 nm or less, or 20 nm or less. More specifically, the diameter of the macropores may be 10 nm to 19 nm, 10 nm to 18 nm, 12 nm to 18 nm, 13 nm to 17 nm, or 14 nm to 15 nm.
[0111] The diameter of the micropores may be measured by a method known in the art for measuring the diameter of pores in a porous material, and the method is not particularly limited. For example, the diameter of the micropores may be measured using a scanning electron microscope (SEM), a field-emission electron microscope (FE-SEM), or a laser diffraction method.
[0112] In one aspect of the present invention, when the total number of macropores is greater than the total number of nanopores, the carbon composite may be mixed with an active material to have a more advantageous effect in mediating the activation of the lithium polysulfide conversion reaction.
[0113] In another aspect of the present invention, when the number of pores having a pore diameter of less than 10 nm among all pores in the carbon composite is defined as N(nano) and the number of pores having a pore diameter of 10 nm or more is defined as N(macro), the ratio of N(macro) to N(nano) is N(macro) / N(nano), which may be 1 or greater.
[0114] In one embodiment of the present invention, the average particle size (D 50 ) can be, for example, 0.5 μm to 200 μm, 0.5 μm to 200 μm, 1 μm to 150 μm, or 10 μm to 150 μm.
[0115] In one embodiment of the present invention, for utility in lithium-sulfur batteries, the BET specific surface area of the carbon composite is, for example, 200 m 2 / g or more, but is not limited thereto.
[0116] Specifically, the upper limit of the BET specific surface area of the carbon composite is not particularly limited, but it is preferably, for example, 200 m 2 / g or more, 300m 2 / g or more, 400m 2 / g or more, 500m 2 / g or more, 600m 2 / g or more, 700m 2 / g or more 1,500m 2 / g or less, 1,000m 2 / g or less, 900m 2 / g or less, 800m 2 / g or less, 780m 2 / g or less, 750m 2 The carbon composite according to the present invention has a large number of micropores, and the catalyst supported thereon may have a form in which a transition metal having a single atomic size is dispersed in a porous carbon material and / or an organic support, and thus has an advantage of having a very large specific surface area.
[0117] The BET specific surface area is measured by the BET method and may indicate a value measured according to a known method for measuring a BET specific surface area. For example, the BET specific surface area may be a value calculated from the amount of nitrogen gas adsorbed at liquid nitrogen temperature (77K) using BELSORP-mino II manufactured by BEL Japan.
[0118] In one embodiment of the present invention, the pore volume of the carbon composite is, for example, 1 to 10 cm 3 Specifically, the pore volume of the carbon composite may be 1 to 10 cm. 3 / g, 2-8cm 3 / g, 3-6cm 3 / g, 4~5cm 3 / g, 1-3cm 3 / g, or 1-2cm 3 / g, but is not limited thereto.
[0119] The pore volume may be, for example, a value calculated and measured by N2 isotherm analysis obtained based on the adsorption of liquid nitrogen.
[0120] In one embodiment of the present invention, the carbon composite has a Raman peak intensity ratio (I G / I D For example, the ratio of I to I may be 1 or less. G / I D The ratio may be 0.1 to 1, 0.5 to 1, or 0.8 to 1.0. G / I D When the ratio is within the above range, the porous carbon material can exhibit advantageous effects in terms of catalyst supporting efficiency and / or sulfur doping efficiency, but the present invention is not limited thereto.
[0121] The Raman peak intensity ratio is an I obtained from the spectrum of the carbon composite obtained by Raman spectroscopy. G and I D In the resulting spectrum, I G means the peak of the crystalline part (G-peak, 1573 / cm), and I D means the peak of the amorphous part (D-peak, 1309 / cm). Therefore, in this case, I G / I D The smaller the ratio, the lower the crystallinity.
[0122] In one embodiment of the present invention, the carbon composite may have a transition metal content of, for example, 1 wt% to 20 wt%, specifically 1 wt% to 10 wt%, based on the total weight of the carbon composite. When the transition metal content is within the above range, it may be advantageous in that the transition metal is well dispersed in a single atomic size to increase the specific surface area of the carbon composite while exhibiting an excellent catalytic effect of the carbon composite. For example, when the transition metal content in the carbon composite exceeds the above range, the carbon composite may include the transition metal in the form of metal particles by forming metallic bonds between the transition metals.
[0123] In one embodiment of the present invention, the carbon composite may have a sulfur (S) content of, for example, 0.1 wt % to 10 wt %, specifically 1 wt % to 5 wt %, based on the total weight of the carbon composite. When the sulfur content is in the above range, it may be advantageous in terms of exhibiting an effect of increasing the catalytic efficiency of the transition metal.
[0124] In another embodiment of the present invention, as described above, the carbon composite may include iron as a transition metal, and the catalyst may have a form in which iron is dispersed on an organic support in a single atomic size, and the iron forms a ligand with four surrounding nitrogen atoms. That is, when such a structure is expressed as Fe-N4, sulfur doped in a porous carbon material is present around the Fe-N4, and sulfur capable of forming a coordinate bond with the iron of Fe-N4 may be present in the structure of -C-SO2-C- (first structure) and / or -CSC- (second structure). In this case, the ratio of the first structure / second structure may be 1 or less as described above, specifically, 0.1 to 0.7. The content of sulfur in the carbon composite may be determined within a range satisfying the above-mentioned ratio. In this case, the ratio of the first structure / second structure may be expressed as a molar ratio as described above.
[0125] The ratio of the first structure / second structure may be, for example, 1 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, 0.3 or less, 0.2 or less, or 0.15 or less. The ratio of the first structure / second structure may be, for example, 0.01 or more, 0.05 or more, or 0.1 or more. For example, the ratio of the first structure / second structure may be 0.01 or more and 1 or less, 0.05 or more, 0.8 or less, 0.10 or more and 0.7 or less, 0.10 or more and 0.5 or less, or 0.10 or more and 0.2 or less, but the present invention is not limited thereto.
[0126] The carbon composite of the present invention as described above can exchange electrons with transition metals around a transition metal-containing catalyst and can provide additional binding sites with lithium polysulfide. Therefore, the carbon composite can be used in the positive electrode of a lithium-sulfur battery to enhance battery efficiency, but the mechanism of the present invention is not limited thereto.
[0127] According to one aspect of the present invention, the carbon composite is a support for supporting a sulfur-based compound, which is a positive electrode active material, and may be used as a positive electrode active material by being additionally composited with the sulfur-based compound, or the carbon composite itself may be used as a substitute for a conductive material.
[0128] In particular, the carbon composite of the present invention may exhibit the effect of significantly improving the atomic utilization rate of the carbon composite by dispersing the transition metal at a single atomic size, but the mechanism of the present invention is not limited thereto.
[0129] Another aspect of the present invention provides a method for producing the above-mentioned carbon composite.
[0130] A method for producing a carbon composite according to another aspect of the present invention includes the steps of: (S1) doping at least one sulfur atom in a porous carbon material; and (S2) immersing the result of step (S1) in a transition metal-containing precursor solution and then removing the solvent. Specifically, step (S1) includes a step of heat-treating the porous carbon material in contact with the sulfur-doped precursor.
[0131] The step (S1) is a step for doping a porous carbon material with sulfur to form an electron exchangeable bond (EEB) site for the catalyst.
[0132] In one embodiment of the present invention, the step (S1) may include, for example, heat treating the porous carbon material after impregnating it with a sulfur-containing solution that includes a sulfur-doped precursor.
[0133] In one embodiment of the present invention, the step (S1) may be performed, for example, by impregnating the porous carbon material with a sulfur-containing solution, grinding the material until the solvent evaporates, and then heat treating the material, but the present invention is not limited thereto.
[0134] In one embodiment of the present invention, wetting the porous carbon material with the sulfur-containing solution may be performed, for example, by impregnating the porous carbon material with the sulfur-containing solution or by immersing the porous carbon material in the sulfur-containing solution, but the present invention is not limited thereto.
[0135] In one embodiment of the present invention, the heat treatment may be carried out at, for example, 800° C. to 1,000° C. to form a low ratio of —C—SO 2 —C— (first structure) / —CSC- (second structure) at the EEB site.
[0136] In one embodiment of the present invention, the heat treatment may include increasing the temperature while maintaining the temperature at a constant rate selected from the range of 2° C. / min to 10° C. / min.
[0137] In one embodiment of the present invention, the heat treatment may be carried out while increasing the temperature at a rate of 5° C. / min.
[0138] In one aspect of the present invention, the porous carbon material is contacted with a sulfur-containing solution as described above, and then the porous carbon is uniformly doped with sulfur by crushing and heat treatment, thereby forming a uniform EEB in the porous carbon. As a result, the catalyst described below may have a morphology in which the transition metal is uniformly dispersed in a single atomic size, but the manufacturing method of the present invention is not limited thereto.
[0139] The sulfur-containing solution may be a solution in which a sulfur-doped precursor is dissolved in a solvent. The sulfur-doped precursor may be, for example, dibenzyl disulfide (DBDS), sodium metabisulfite (Na2S2O5), sodium pyrosulfate (Na2S2O7), sodium thiosulfate (Na2S2O3), thiourea (CH4N2S), sodium sulfide (Na2S), potassium thiocyanate (KSCN), benzyl mercaptan (C7H8S), benzothiophene (C8H6S), dibenzothiophene (C8H6S), or the like. 12 The solvent may be, for example, sulfur-doped precursor, H8S, dibenzohiophene, or a mixture thereof. The solvent is not particularly limited and may be appropriately selected from solvents that are excellent in wettability with the porous carbon material while being a solvent for the sulfur-doped precursor.
[0140] According to one aspect of the present invention, the form and structure of the porous carbon material doped with sulfur may vary depending on the type of the sulfur-doped precursor. In this case, since sulfur serves as an EEB site and can abundantly supply electrons to the transition metal, the doping with sulfur may be performed using dibenzyl disulfide dissolved in an alcohol-based solvent such as ethanol.
[0141] According to one embodiment of the present invention, the sulfur doping may be performed using dibenzyl disulfide, and the ratio of -C-SO2-C- (first structure) / -CSC- (second structure) in the produced carbon composite may be 0.1 to 0.5.
[0142] According to another embodiment of the present invention, the sulfur doping may be performed using sodium sulfite, and the ratio of -C-SO2-C- (first structure) / -CSC- (second structure) in the produced carbon composite may be 0.5 to 1.
[0143] The step (S2) may include preparing a precursor solution for preparing a catalyst supported on the sulfur-doped porous carbon material.
[0144] In one embodiment of the present invention, the transition metal-containing precursor solution is a precursor solution for producing a catalyst, and may contain an organic solvent and a precursor compound of a transition metal.
[0145] In one embodiment of the present invention, the transition metal-containing precursor solution is a precursor solution for producing a catalyst, and may contain an organic solvent, a precursor compound of a nonmetallic element, and a precursor compound of a transition metal.
[0146] In one embodiment of the present invention, the precursor compound of the transition metal may be, for example, an oxide, halide, acetide, nitrate, sulfate, cyanide, a salt of a saturated or unsaturated carbon chain fatty acid, or a phosphonate, of a transition metal, or a mixture of two or more of these.
[0147] In one embodiment of the invention, the transition metal halide can be, for example, a transition metal fluoride, a transition metal chloride, a transition metal bromide, or a transition metal iodide.
[0148] In other embodiments of the invention, the precursor solution may include iron trichloride (FeCl3), ferrocene, iron acetylacetonate, iron nitrate, ferrous sulfate, potassium iron ferricyanide, or a mixture of two or more thereof.
[0149] In one embodiment of the present invention, the precursor compound of the non-metallic element may be an organic compound containing at least one non-metallic element.
[0150] In one embodiment of the present invention, the organic compound containing at least one nonmetallic element is a compound containing the nonmetallic element described above. The nonmetallic element may be, for example, nitrogen (N), and the organic compound containing nitrogen may be, for example, 1,10-phenanthroline, polyaniline, polydopamine, melamine, carbon nitride (g-CN), phenylenediamine, or a mixture of two or more of these.
[0151] In one embodiment of the present invention, the organic solvent is a solvent for the organic compound containing at least one nonmetallic element and the transition metal halide, and may be appropriately selected and used, without any particular limitation.
[0152] In one embodiment of the present invention, the molar ratio of the precursor compound of the nonmetallic element to the transition metal halide in the precursor solution may be, for example, but is not limited to, 50:1 to 1:1, 40:1 to 1:1, 20:1 to 1:1, 10:1 to 1:1, or 5:1 to 1:1.
[0153] In one embodiment of the present invention, the molar ratio of the precursor compound of the non-metal element to the transition metal halide in the precursor solution may be, for example, 4:1.
[0154] In one embodiment of the present invention, the method may further include a step of preparing a transition metal-containing precursor solution before the step (S2). In this case, the step of preparing a transition metal-containing precursor solution can be carried out in any order in relation to the step (S1). For example, the step of preparing the transition metal-containing precursor solution can be carried out after the step (S1), the step of preparing the transition metal-containing precursor solution can be carried out after the step of preparing the transition metal-containing precursor solution, or the step of preparing the transition metal-containing precursor solution can be carried out while simultaneously carrying out the step (S1). In this way, the order of carrying out the step (S1) and the step of preparing the transition metal-containing precursor solution is not particularly limited.
[0155] The step (S2) is a step of disposing at least one catalyst containing a transition metal on at least one of the outer surface and the inner surface of the pores of the at least one sulfur-doped porous carbon material prepared in the step (S1).
[0156] To this end, the step (S2) includes a step of immersing the result of the step (S1) in the transition metal-containing precursor solution and then removing the solvent.
[0157] In one aspect of the present invention, the step (S2) may include a step of impregnating the result of the step (S1) with the transition metal-containing precursor solution, followed by pulverizing and drying. The drying may be performed at, for example, 70° C. to 100° C., but is not limited thereto. According to another aspect of the present invention, the method may further include a step of performing a heat treatment at, for example, 800° C. to 1,000° C. after the drying.
[0158] In one embodiment of the present invention, after the step (S2), the method may further include a step (S3) of cooling the resultant obtained from the step (S2) at room temperature and then treating it with an acid.
[0159] According to the above-mentioned method, a carbon composite can be produced, which includes at least one sulfur-doped porous carbon material and at least one catalyst containing one or more transition metals, and in which the catalyst is located on at least one of an outer surface and inner surfaces of pores of the at least one sulfur-doped porous carbon material.
[0160] According to yet another aspect of the present invention, there is provided a positive electrode including a positive electrode active material that includes the above-mentioned carbon composite and a sulfur-based compound.
[0161] The positive electrode may include, as a positive electrode active material, a composite formed by using the above-mentioned carbon composite as a support for a positive electrode active material and mixing the carbon composite with a sulfur-based compound as a positive electrode active material.
[0162] In one embodiment of the present invention, the sulfur-based compound is, for example, sulfur (S8), lithium sulfide (Li2S), lithium polysulfide (Li2S x , 2≦x≦8), a disulfide compound, or a mixture of two or more of these, but is not limited thereto.
[0163] In one embodiment of the present invention, the carbon composite and the sulfur-based compound are determined according to the content of sulfur in the carbon composite and the type of the sulfur-based compound, and are not particularly limited, but for example, the carbon composite and the sulfur-based compound may be mixed in a content ratio of 1:9 to 9:1. Specifically, the carbon composite and the sulfur-based compound may be mixed in a content ratio of 1:9 to 5:5, more specifically, 2:8 to 4:6.
[0164] In one embodiment of the present invention, the positive electrode active material may be formed by mixing the carbon composite and a sulfur-based compound, followed by heat treatment. The heat treatment may be performed at a temperature of, for example, 130° C. to 180° C., specifically, 150° C. to 160° C.
[0165] In one embodiment of the present invention, the positive electrode for a lithium-sulfur battery may further include a binder in addition to the positive electrode active material including the carbon composite and the sulfur-based compound. The binder is not particularly limited as long as it is a binder used in a positive electrode of a lithium-sulfur battery.
[0166] In another embodiment of the present invention, the positive electrode for a lithium-sulfur battery may further include, in addition to the positive electrode active material and the binder, a conductive material, an additive, etc. In this case, the binder, the conductive material, and the additive may be conventional materials, and therefore the specific types thereof will not be described.
[0167] In yet another aspect of the present invention, the positive electrode for a lithium-sulfur battery may include a positive electrode current collector and a positive electrode active material layer in which the positive electrode active material is applied to one or both sides of the current collector together with a binder.
[0168] In this case, the positive electrode current collector is not particularly limited as long as it has high conductivity and does not induce chemical changes in the battery.
[0169] In one embodiment of the present invention, a positive electrode containing the carbon composite can exhibit excellent effects in terms of initial capacity and cycle stability, but the effects of the present invention are not limited thereto.
[0170] In one embodiment of the present invention, the positive electrode for a lithium-sulfur battery has a capacitance of, for example, 1.0 mg / cm 2 For example, the sulfur loading in the positive electrode for the lithium-sulfur battery may be 1 mg / cm or more. 2 More than 1.5mg / cm 2 More than 2mg / cm 2 More than 2mg / cm 2 ~10mg / cm 2 At the same time, it is possible to exhibit the effect of showing driving stability.
[0171] According to another aspect of the present invention, there is provided a lithium-sulfur battery comprising a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte. The positive electrode comprises the carbon composite and a sulfur-based compound as a positive electrode active material.
[0172] In one aspect of the present invention, the negative electrode, the separator, and the electrolyte may be any material that can be used in a lithium-sulfur battery without any particular limitation as long as the object of the present invention is not impaired. Therefore, the specific types of the negative electrode, the separator, and the electrolyte may be omitted.
[0173] In one aspect of the present invention, the lithium-sulfur battery may have, but is not limited to, a coin type, a cylindrical type, a pouch type, a rectangular type, etc. In addition, the lithium-sulfur battery may be used not only as a battery cell used as a power source for a small device, but also as a unit battery of a medium- to large-sized battery module including a plurality of battery cells, and there is no particular limitation on the form of use.
[0174] In one embodiment of the present invention, a lithium-sulfur battery using a positive electrode containing the carbon composite is excellent not only in terms of initial capacity and cycle stability but also in terms of battery energy density, but the effects of the present invention are not limited thereto.
[0175] In one aspect of the present invention, the lithium-sulfur battery can exhibit an effect of significantly improving energy density by increasing the sulfur loading amount in the electrode and reducing the amount of electrolyte, but the effect of the present invention is not limited thereto.
[0176] In one embodiment of the present invention, the lithium-sulfur battery may have an electrolyte / sulfur (E / S) ratio of 10 μL / mg or less. For example, the E / S ratio of the lithium-sulfur battery may be 10 μL / mg or less, 8 μL / mg or less, 6 μL / mg or less, 4 μL / mg or less, or 2 μL / mg or less. Conventionally, there was a limit to lowering the E / S ratio due to low activity of the positive electrode, but the present invention has an effect of stably lowering the E / S ratio, so that the E / S ratio of the lithium-sulfur battery may exceed the above range, and it is obvious to those skilled in the art that there is no lower limit, and the present invention is not limited thereto.
[0177] In another aspect of the invention, the lithium-sulfur battery may have an electrolyte / capacity (E / C) ratio of 10 μL / mAh or less. For example, the lithium-sulfur battery cell may have an E / C ratio of 10 μL / mAh or less, 9 μL / mAh or less, 8 μL / mAh or less, 7 μL / mAh or less, 5 μL / mAh or less, or 4 μL / mAh or less, but the invention is not limited thereto. The lithium-sulfur battery may have an electrolyte / capacity (E / C) ratio of 1 μL / mAh or more, but the invention is not limited thereto.
[0178] According to yet another aspect of the present invention, there is provided a positive electrode containing the above-mentioned carbon composite as a positive electrode additive and a sulfur-based compound as a positive electrode active material.
[0179] In one embodiment of the present invention, apart from the aspect of the present invention in which the carbon composite is used as a support and is included in a positive electrode in the form of a positive electrode active material formed by compounding with a sulfur-based compound, the carbon composite can be included in the positive electrode as an additive substituting for a conductive material.
[0180] In one aspect of the present invention, when the carbon composite is used as a positive electrode additive, not only can the capacity of the battery be improved, but also the reactivity with lithium polysulfide can be improved, thereby improving the battery performance.
[0181] In one embodiment of the present invention, when the carbon composite is used as a positive electrode additive, the carbon composite may be included in an amount of 1 to 25 wt %, for example, 1 to 15 wt %, or 1 to 10 wt %, based on the total weight of the positive electrode active material, the binder, and the carbon composite included in the positive electrode active material layer, but is not limited thereto.
[0182] In one aspect of the present invention, the positive electrode can be a sulfur-based compound as a positive electrode active material, or a sulfur-based compound supported on a normal carbon support. The sulfur-based compound is the same as the configuration of the positive electrode according to the above aspect. The normal carbon support can be, for example, carbon nanotubes, but is not limited thereto.
[0183] According to yet another aspect of the present invention, there is provided a lithium-sulfur battery including a positive electrode using the carbon composite as a positive electrode additive as described above, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte.
[0184] According to yet another aspect of the present invention, there is provided a battery including at least one of a positive electrode and a negative electrode containing the carbon composite as described above. In this case, the battery may include a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, and is not particularly limited to a lithium-sulfur battery.
[0185] In this case, the configuration of the battery according to the above aspect is applied to the configurations other than the negative electrode, the separator, the electrolyte, and the carbon composite of the positive electrode.
[0186] FIG. 2a shows a schematic diagram of a flow chart of a method for doping at least one sulfur atom into porous carbon, forming a transition metal-containing catalyst to prepare a carbon composite, and then mixing the carbon composite with a sulfur-based compound to prepare a cathode active material according to one embodiment of the present invention.
[0187] Hereinafter, a method for producing a carbon composite according to one embodiment of the present invention and a method for producing a positive electrode active material using the same will be described in detail with reference to examples. However, the following examples are merely for the purpose of illustrating the present invention, and the scope of the present invention is not limited to these examples.
[0188] Production Example 1. Synthesis of porous carbon material (MSU-FC) The porous carbon material was synthesized using a hard template method according to the following steps.
[0189] First, poly(ethylene glycol)-block-polypropylene glycol)-block-poly(ethylene glycol) (P123, Mn: ~5800 g / mol, Sigma-Aldrich) was dissolved in distilled water (160 ml) and glacial acetic acid (99.8%, SAMCHUN Pure Chemical Co., Ltd.) (4.58 ml). Next, mesitylene (Merck Millipore) (9.26 ml) was added dropwise and stirred for 1 hour to prepare a P123 solution.
[0190] Sodium silicate (Sigma Aldrich) (15.5 ml) was dissolved in distilled water (240 ml) to prepare a sodium silicate solution. The prepared sodium silicate solution was added to the P123 solution prepared above, stirred for 5 minutes, and then stored at 40°C for 20 hours without stirring. It was then aged in an oven at 100°C for 24 hours. The aged solution was filtered and redissolved in a mixture of distilled water (200 ml) and HCl solution (35.0-37.0%, SAMCHUN Pure Chemical Co., Ltd.) (5 ml). After 3 hours, the solution was filtered again and calcined at 550°C for 4 hours to obtain mesoporous silica (MSU-F-SiO2).
[0191] The obtained mesoporous silica was uniformly dispersed in ethanol and mixed with AlCl3·6H2O (98%, Kanto Chemical Co., Ltd.) (0.21 g) to obtain a uniform mixture. The mixture was then dried in an oven at 60 °C to remove the ethanol, and the mixture was calcined at 550 °C for 4 hours to obtain mesoporous silica with Al acid sites introduced (Al-MSU-F-SiO2).
[0192] The Al-MSU-F-SiO2 hard mold was impregnated with furfuryl alcohol (Sigma-Aldrich) as a carbon precursor, and then heat-treated at 850°C for 4 hours under an Ar atmosphere. After cooling to room temperature, the Al-MSU-F-SiO2 mold was etched with a HF solution (JT Baker) to produce the porous carbon material (MSU-FC) of Production Example 1.
[0193] Example 1. Preparation of carbon composite (FeNC-EEB-1) Step 1. Doping of porous carbon material with sulfur (creation of EEB sites) Dibenzyl disulfide (DBDS, 98%) was dissolved in ethanol (100 ml) to prepare a DBDS solution.
[0194] The porous carbon material (MSU-FC) prepared above was uniformly impregnated with the DBDS solution and repeatedly ground until the ethanol was completely evaporated. The DBDS-impregnated porous carbon (DBDS-impregnated MSU-FC) was then dried at 80°C for 1 hour and then heat-treated at 900°C for 1 hour in an Ar atmosphere to form EEB sites with a low -SO2 / -S molar ratio.
[0195] Step 2. Introducing the transition metal catalyst In order to support a transition metal catalyst on the outer surface of the porous carbon in which the EEB sites were formed and on the inner surface of the pores, a transition metal-containing precursor solution was prepared by dissolving FeCl3·6H2O (Sigma-Aldrich) and 1,10-phenanthroline (99%, Sigma-Aldrich) in ethanol. The precursor solution was then immersed in the porous carbon material in which the EEB sites were formed and then crushed. The mixture was dried at 80°C for 1 hour and then heat-treated at 900°C for 1 hour under an Ar atmosphere. After cooling to room temperature, the mixture was stirred with 1M HCl to remove the aggregated Fe metal residue, and the title carbon composite (FeNC-EEB-1) was prepared.
[0196] Example 2. Preparation of carbon composite (FeNC-EEB-2) A carbon composite (FeNC-EEB-2) was produced in the same manner as in Example 1, except that Na2S2O5 (97%, Sigma-Aldrich) was used instead of DBDS for the formation of EEB sites.
[0197] Comparative Example 1. Production of carbon composite (FeNC) A carbon composite (FeNC) was produced in the same manner as in Example 1, except that step 1 was omitted to introduce a transition metal catalyst without forming an EEB site.
[0198] [Confirmation of sulfur doping] X-ray spectroscopy (XPS) (VG Scientific Escalab 250, Al Kα) was used to obtain 2p spectra of sulfur atoms (S) in the carbon composites of Examples 1 and 2, and the results are shown in FIG. 2b (Example 1) and FIG. 2c (Example 2), respectively.
[0199] 2b and 2c, it was confirmed that both Example 1 and Example 2 exhibited two peaks characteristic of -S, 163.7 eV (CSC 2p 3 / 2) and 164.9 eV (CSC 2p 1 / 2), in the -CSC- structure formed by doping sulfur atoms in porous carbon, and a peak characteristic of -SO2, 168.0 eV (Oxidized S), in the -C-SO2-C- structure formed by doping sulfur dioxide.
[0200] This confirmed that both Example 1 and Example 2 contained a structure in which sulfur was doped in the porous carbon.
[0201] Next, the Fe content and the molar ratio of -SO2 / -S structure of the carbon composites of Example 1, Example 2, and Comparative Example 1 were measured using inductively coupled plasma atomic emission spectroscopy (ICP-AES), and the results are shown in Figure 2d.
[0202] 2d, it was confirmed that the -SO2 / -S molar ratios at the EEB site were different between Example 1 and Example 2. Specifically, the -SO2 / -S molar ratio in Example 1 was 0.12, and the -SO2 / -S molar ratio in Example 2 was 0.63, which was about 5 times higher than that in Example 1. This is presumed to be because Na2S2O5, which is a precursor for sulfur doping in Example 2, has a higher oxygen fraction than DBDS, and therefore forms -SO2 species more stably at high temperatures.
[0203] In addition, the mapping images by the energy dispersive X-ray analyzer (EDS: Energy Dispersive Spectroscopy) according to Example 1 and Example 2 are shown in FIG. 3. The mapping images by EDS were obtained by the distribution results of Fe single atoms and other components using a high performance TEM (HR-TEM; Titan cubed G2 60-300). According to FIG. 3, it was confirmed that Fe, N, C, S and O atoms in each of Example 1 and Example 2 were uniformly distributed along the particles. This confirmed that an EEB site was formed in the carbon composite by doping with the transition metal-containing catalyst and sulfur. In particular, according to FIG. 3, it was confirmed that the nearest atomic distance between the Fe element and the S element was formed to be 2 nm or less in the carbon composite of Example 1 and Example 2.
[0204] [Structural analysis of carbon composites] The structures of the carbon composites produced above in Example 1, Example 2, and Comparative Example 1 were confirmed by the following method.
[0205] Microscopic observation For the carbon composites of Example 1, Example 2, and Comparative Example 1, images obtained using an SEM (S-4800 field emission, Hitachi, Ltd.) and a TEM (G2 F30 S-Twin, Tencai) are shown in Fig. 4. In Fig. 4, FeNC represents the carbon composite of Comparative Example 1, FeNC-EEB-1 represents the carbon composite of Example 1, and FeNC-EEB-2 represents the carbon composite of Example 2, and in each figure, the left image represents an SEM image and the right image represents a TEM image.
[0206] Analysis of pore characteristics For each of the carbon composites of Example 1, Example 2, and Comparative Example 1, the pore diameter (left) and relative pressure (right) were determined by nitrogen physical adsorption analysis, and the results are shown in FIG.
[0207] Specifically, the specific surface area and pore size of the comparative examples and examples were analyzed as follows.
[0208] First, the specimen was pretreated by drying it overnight in vacuum at 120°C to remove moisture and other substances physically adsorbed in the pores. Then, liquid nitrogen at 77K was physically adsorbed on the surface and pores of the specimen until the pressure equilibrated in vacuum. The specific surface area of the porous material was calculated using the BET (Brunauer-Emmett-Teller) method based on the measured N2 isotherm. Furthermore, the pore volume value was calculated using the BJH (Barrett-Joyner-Halenda) method based on the obtained N2 isotherm.
[0209] The results of measuring the surface area, pore diameter and pore volume of each of the carbon composites of Example 1, Example 2 and Comparative Example 1 are shown in Table 1 below.
[0210] As can be seen from Fig. 5, the pore diameter distribution was bimodal. In Table 1 below, the peak appearing at the smaller diameter is shown as the first pore diameter peak, and the peak appearing at the larger diameter is shown as the second pore diameter peak.
[0211] [Table 1]
[0212] According to the results of FIG. 4, FIG. 5 and Table 1, each of the carbon composites of Example 1, Example 2 and Comparative Example 1 has a porous structure and a BET specific surface area of 700 m 2 / g or more and were confirmed to contain pores of 4 to 5 nm and 10 to 15 nm, respectively.
[0213] Confirmation of transition metal distribution For each of Comparative Example 1, Example 1, and Example 2, images obtained using a high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) are shown in FIG. 6. The HAADF-STEM images were obtained using a high-performance TEM (HR-TEM; Titan cubed G2 60-300) to obtain the distribution results of Fe single atoms and other components. According to FIG. 6, it was confirmed that in Comparative Example 1, Example 1, and Example 2, the transition metal Fe was dispersed in the porous carbon at the size of a single atom.
[0214] In addition, the results of Fourier-transformed extended X-ray absorption fine structure (FT-EXAFS) for Comparative Example 1, Example 1, and Example 2 are shown in Figure 7. In order to compare the chemical state of the iron element distributed in the carbon composite with the chemical state of iron metal, the evaluation results for Fe foil are also shown in Figure 7.
[0215] 7, Fe-Fe metal bonds (2.2 Å) were confirmed in the Fe foil, whereas the Fe-Fe metal bonds disappeared and Fe-N (1.4 Å) and Fe-C (2.4 Å) peaks were newly formed in Comparative Example 1, Example 1, and Example 2. This confirmed that the catalyst (Fe-NC) present in Comparative Example 1, Example 1, and Example 2 does not contain Fe-Fe metal bonds, i.e., Fe metal particles.
[0216] [Confirmation of catalytic function of carbon composites] FIG. 8 shows a graph obtained by using Fe K-edge XANES (X-ray absorption near-edge structure) analysis for the carbon composites of Example 1, Example 2, and Comparative Example 1.
[0217] 8, it was confirmed that the white line intensity of Example 1 was lower than that of Comparative Example 1, and the white line intensity of Example 2 was higher than that of Comparative Example 2. That is, it was confirmed that Example 1 has a low -SO2 / -S ratio and shows an upshift of the Fe d-band center, which may result in the activity of electron transfer from the EEB site to Fe.
[0218] On the other hand, Example 2 had a high -SO2 / -S ratio and showed a downshift of the Fe d-band center, and it was confirmed that this may have activity in which electrons move from Fe to the EEB site.
[0219] This confirmed that the presence of a sulfur-doped structure around the catalyst that can form coordinate bonds with transition metals, i.e., the d-orbital level of the carbon composite can be adjusted by electron exchange depending on the -SO2 / -S ratio.
[0220] [Manufacturing lithium-sulfur coin batteries] In order to confirm the sulfur and polysulfide conversion reaction activity of the carbon composite prepared above, a lithium-sulfur coin-type battery was prepared as follows.
[0221] Example 3 Cathode manufacturing The carbon composite (FeNC-EEB-1) of Example 1 produced above in an amount of 30 wt % and sulfur (sulfur powder, manufactured by Sigma-Aldrich) in an amount of 70 wt % were mixed and heated at 155° C. for 8 hours to obtain a positive electrode active material.
[0222] To prepare a working electrode, the prepared positive electrode active material and PVDF (polyvinylidene fluoride) as a binder were mixed in a weight ratio of 9:1 using NMP (N-methyl-2-pyrrolidone) solvent to prepare a positive electrode slurry.
[0223] The prepared positive electrode slurry was coated on a carbon-coated Al foil and then dried for 8 hours at 60° C. The electrode was then pressed and cut into coins to prepare positive electrodes.
[0224] Battery manufacturing A positive electrode, a negative electrode, and a separator between the positive electrode and the negative electrode were interposed, and the resultant was placed in a case together with an electrolyte to prepare a battery.
[0225] The cathode prepared above was used as the cathode, and a porous polypropylene membrane (Celgard 2400, Welcos Ltd) was used as the separator. Lithium metal (200 μm thick) was used as the reference electrode and counter electrode. The electrolyte used was a solution of a 1:1 volumetric mixture of dimethoxymethane and 1,3-dioxolane (DME / DOL) (PANAX E-TEC Co., Korea), containing 1.0 M LiTFSI (lithium salt of bis(trifluoromethane)sulfonamide) as the electrolyte and 2.0 wt% LiNO3 (99.99% metal base, Sigma-Aldrich) as the additive.
[0226] The sulfur loading in the positive electrode is 2.0 mg / cm 2 and the E / S ratio of the battery was 10 μL / mg.
[0227] Example 4 A battery was manufactured in the same manner as in Example 3, except that the carbon composite of Example 2 (FeNC-EEB-2) was used in the manufacture of the positive electrode.
[0228] Comparative Example 2 A battery was manufactured in the same manner as in Example 3, except that Comparative Example 1 (FeNC) was used as the carbon composite in manufacturing the positive electrode.
[0229] Manufacturing Example 2 A battery was manufactured in the same manner as in Example 3, except that the porous carbon material (MSU-FC) of Preparation Example 1 was used instead of the carbon composite when manufacturing the positive electrode.
[0230] [Performance evaluation of lithium-sulfur coin-type batteries] Using the lithium-sulfur coin-type battery prepared above, the redox kinetic activity of lithium sulfide (LiS) was evaluated as follows.
[0231] First, Fig. 9a shows Tafel plots obtained to evaluate the oxidation-reduction kinetics of sulfur. Fig. 9a shows that the Tafel plot of Example 3 in the positive electrode reaction is much lower than that of Comparative Example 2, whereas the Tafel plot of Example 4 is slightly lower than that of Comparative Example 2. On the other hand, in the negative electrode reaction, both Example 3 and Example 4 show lower Tafel slots than Comparative Example 2, which proves that the doped sulfur around the catalyst, i.e., -SO2 / -S EEB sites, improve the oxidation-reduction kinetics of sulfur.
[0232] Next, to better understand the electrochemical kinetics of sulfur with EEB sites on the nucleation / decomposition behavior of lithium sulfide in the batteries of Example 3 and Example 4, a constant voltage analysis was performed and the results are shown in Figures 9b and 9c, in which the capacity was calculated based on the weight of sulfur in the electrodes.
[0233] According to Fig. 9b, the maximum current during constant voltage discharge at 2.05 V is m The values were 227s (Example 3), 320s (Example 4), and 400s (Comparative Example 2), respectively. m The values are expressed as the nucleation density (N0) and growth rate (k 2 Considering that the capacity of the battery is closely related to the lithium sulfide nucleation capacity, it was confirmed that the improvement of the lithium sulfide nucleation capacity in the battery of Example 3 leads to a higher lithium sulfide nucleation capacity (213.3 mAh / g). Next, it was confirmed that the capacity of Example 4 (196.8 mAh / g) is slightly lower than that of Example 3 (213.3 mAh / g), but has a capacity characteristic further improved than that of Comparative Example 2 (185.3 mAh / g).
[0234] t m =(2πN0k 2 )-0.5
[0235] According to FIG. 9c, during the constant voltage charging at 2.35 V, Example 3 was faster than Comparative Example 2 (t m : 468s, lower than Li2S dissociation capacity: 323.5mAh / g m (360s) and a high Li2S decomposition capacity (457.2mAh / g). m (489s) and a high Li2S decomposition capacity (381.5mAh / g).
[0236] As a result, (i) it was confirmed that the kinetics of the conversion reaction involving lithium sulfide on the catalyst can be improved by introducing -SO2 / -S EEB sites formed by doping sulfur around the transition metal-containing catalyst, by comparing the results of Comparative Example 2, Examples 3 and 4. In particular, (ii) it was confirmed that the EEB site having a low -SO2 / -S ratio (Example 3) is more effective in promoting the nucleation / decomposition reaction of lithium sulfide on the catalyst than the EEB site having a high -SO2 / -S ratio (Example 4).
[0237] Next, in order to evaluate the charge / discharge performance of the batteries of Comparative Example 2, Example 3, and Example 4, the batteries of Comparative Example 2, Example 3, and Example 4 were subjected to a current density test at 0.2 to 3.0 C rate (1 C rate to 1675 mA / g) and a charge / discharge voltage test at 1.7 to 2.8 V (vs. Li / Li + The charge-discharge performance was evaluated in the voltage range of 100 V to 200 V, and the results are shown in FIG.
[0238] 10(a) shows the initial voltage characteristics at 0.2 C rate of the batteries of Comparative Example 2, Example 3, and Example 4. According to this, it was confirmed that Comparative Example 2 also had a high initial discharge capacity (1125 mAh / g) due to the presence of the catalyst (FeNC), but the batteries of Example 3 (1324 mAh / g) and Example 4 (1179 mAh / g) had higher initial discharge capacities.
[0239] The results in Fig. 10(b) show the results of a battery (Preparation Example 2) in which the positive electrode was prepared using the porous carbon (MSU-FC) of Preparation Example 1 in addition to the FeNC-EEB-1 used as a comparison group. According to the results in Fig. 10(b), it was confirmed that the polarization degree of the batteries of Example 3 (0.17 V) and Example 4 (0.185 V) was further improved compared to Comparative Example 2 (0.205 V).
[0240] Fig. 10(c) shows the results of measuring the rate capability at different current densities of 0.3 to 2.0 C for the batteries of Comparative Example 2, Example 3, and Example 4. According to the results of Fig. 10(c), the rate capability was also measured in the order of Comparative Example 2 < Example 4 < Example 3, and it was confirmed that Example 3 had the best improvement in the rate capability.
[0241] Fig. 11 is a graph showing the results of measuring the discharge capacity while repeating 200 charge / discharge cycles at 0.2 C. According to Fig. 11, it was confirmed that the battery of Comparative Example 2 exhibited a capacity of 864 mAh / g after 200 cycles, whereas the battery of Example 4 exhibited a capacity of 925 mAh / g, which is an increase of about 7% compared to Comparative Example 2, and the battery of Example 3 exhibited a capacity of 1030 mAh / g, which is an increase of about 10% compared to Example 4. As a result, it was confirmed that the batteries of Examples 3 and 4 exhibited high capacity retention rates even after 200 charge / discharge cycles, and had excellent cycle stability.
[0242] FIG. 12 shows that, by additional experiments, the sulfur loading amount was 1.5 mg / cm when the positive electrode of Example 3 was manufactured.2 , 3.5 mg / cm 2 , 5.0 mg / cm 2 The E / S ratio was adjusted to 4.0 μL / mg, and the discharge capacity was measured after 100 charge / discharge cycles at a rate of 0.1 C. Figure 12 shows that the use of the FeNC-EEB-1 carbon composite showed excellent performance of the lithium-sulfur battery even under harsh conditions.
[0243] From the above results, it was confirmed that the catalysts incorporating -SO2 / -S EEB sites formed by doping sulfur around the transition metal-containing catalyst have excellent effects on high capacity, cycle stability, discharge capacity ratio, and low polarity of lithium-sulfur batteries.
[0244] In particular, it was confirmed that carbon composites with EEB sites with a low -SO2 / -S ratio were more effective in improving the performance of lithium-sulfur batteries than carbon composites with EEB sites with a high -SO2 / -S ratio. Additional experiments confirmed that this is because the -S structure around the catalyst is more effective than the -SO2 structure in adjusting the binding energy of LiPS and the energy barrier of the conversion reaction between Li2S4 and Li2S.
[0245] [Battery manufacturing] Example 5 Cathode manufacturing Carbon nanotubes (CNT, BET specific surface area 150-350m 2 % of ZnO (polyvinyl chloride / g) supported with 75 wt % of sulfur (sulfur powder, manufactured by Sigma-Aldrich) to obtain a positive electrode active material.
[0246] The positive electrode active material produced above and carbon nanotubes (CNTs, BET specific surface area 150 to 350 m) as a conductive material were mixed in NMP (N-methyl-2-pyrrolidone) solvent. 2 / g), the carbon composite (FeNC-EEB-1) prepared in Example 1 as an additive, and PVDF (polyvinylidene fluoride) as a binder were mixed in a weight ratio of 90:2.5:2.5:5, respectively, to prepare a positive electrode slurry.
[0247] The prepared positive electrode slurry was coated on a carbon-coated Al foil and then dried at 60° C. for 8 hours. The electrode was then pressed and cut into coins to prepare positive electrodes.
[0248] Battery manufacturing A battery was produced in the same manner as in Example 3, except that the positive electrode produced above was used.
[0249] The sulfur loading in the positive electrode is 3.5 mg / cm 2 It was.
[0250] Comparative Example 3 A battery was manufactured in the same manner as in Example 5, except that the carbon composite (FeNC-EEB-1) was not mixed, and the positive electrode active material, the conductive material, and the binder were mixed in a weight ratio of 90:5:5 to prepare a positive electrode slurry.
[0251] The sulfur loading in the positive electrode is 3.5 mg / cm 2 It was.
[0252] [Battery performance evaluation] In order to evaluate the charge / discharge performance of the batteries of Example 5 and Comparative Example 3, the batteries of Example 5 and Comparative Example 3 were subjected to a current density test at a rate of 0.1 C and a charge / discharge voltage test at 1.7 to 2.6 V (vs. Li / Li + The charge / discharge performance was evaluated in the voltage range of 100 V to 200 V, and the results are shown in FIG.
[0253] 13 shows the initial voltage characteristics at 0.1C rate of the batteries of Example 5 and Comparative Example 3. It was confirmed that the use of the carbon composite (FeNC-EEB-1) as the positive electrode additive in Example 5 not only improved the initial discharge capacity but also improved the battery reactivity.
[0254] This is presumably because the carbon composite according to the present invention has an effect as a catalytic additive that adsorbs lithium polysulfides and acts as a catalyst to promote the conversion reaction, compared to ordinary conductive materials used in positive electrodes; however, the effects of the present invention are not limited to this.
Claims
1. at least one sulfur-doped porous carbon material; at least one catalyst comprising one or more transition metals; Including, the catalyst is located on at least one of an exterior surface and an interior surface of the pores of the at least one sulfur-doped porous carbon material; the nearest neighbor interatomic distance between the transition metal contained in the catalyst and at least one sulfur doped in the porous carbon material is 2 nm or less; The at least one sulfur-doped porous carbon material includes at least one of a first structure according to the following formula 1 and a second structure according to the following formula 2 in a structure thereof: [Formula 1] -C-SO2-C- [Formula 2] -C-S-C- , a carbon composite.
2. The carbon composite is 200 m 2 The carbon composite according to claim 1 , having a BET specific surface area of 1 / g or more.
3. The carbon composite of claim 1 , wherein the catalyst further comprises the transition metal and at least one nonmetallic element that forms a ligand with the transition metal.
4. The carbon composite of claim 1 , wherein the catalyst further comprises the transition metal, at least one non-metallic element that forms a ligand with the transition metal, and an organic support.
5. The catalyst comprises a single atom catalyst comprising one or more transition metals; 10. The carbon composite of claim 1, wherein said one or more transition metals are dispersed within said carbon composite at single atomic sizes.
6. The carbon composite of claim 1 , wherein the catalyst does not contain any metallic bonds between two or more transition metals.
7. The catalyst comprises particles comprising one or more transition metals; The average diameter of the particles (D 50 2. The carbon composite according to claim 1, wherein the diameter of the transition metal is 1 to 30 nm.
8. The catalyst comprises particles comprising one or more transition metals; The average diameter of the particles (D 50 2. The carbon composite according to claim 1, wherein the diameter of the transition metal atom is 1 to 5 times the diameter of a single atom constituting the transition metal.
9. 2. The carbon composite of claim 1, further comprising zinc (Zn), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zirconium (Zr), niobium (Nb), molybdenum (Mo), technetium (Tc), rubidium (Ru), rhodium (Rh), palladium (Pd), silver (Ag), cadmium (Cd), lanthanum (La), hafnium (Hf), tantalum (Ta), tungsten (W), osmium (Os), iridium (Ir), cerium (Ce), gallium (Gd), scandium (Sc), titanium (Ti), gallium (Ga), indium (In), or two or more of these.
10. The carbon composite of claim 1 , wherein the transition metal comprises iron (Fe).
11. The transition metal includes iron (Fe), The diameter (D 50 2. The carbon composite according to claim 1, wherein the thickness of the first and second nanoparticles is 0.3 nm to 5 nm.
12. The carbon composite according to claim 1 , wherein a molar ratio of sulfur doped in the porous carbon material to one or more transition metals contained in the catalyst is 0.5 to 8.
13. 10. The carbon composite of claim 1, wherein the at least one sulfur is doped in the form of sulfur atoms or sulfur compounds.
14. The carbon composite according to claim 1 , wherein a ratio of the first structure to the second structure is a molar ratio of the first structure / the second structure of 1 or less.
15. The carbon composite according to claim 14, wherein the molar ratio of the first structure to the second structure is 0.1 to 0.
7.
16. Of all the pores in the carbon composite, the number of pores having a pore diameter of less than 10 nm is defined as N (nano) and the number of pores having a pore diameter of 10 nm or more is defined as N (macro). The carbon composite according to claim 1, wherein a ratio of N(macro) to N(nano) [N(macro) / N(nano)] is 1 or more.
17. The Raman peak intensity ratio (I G / I D The carbon composite of claim 1 , wherein the ratio (Ratio) is 1 or less.
18. A method for producing the carbon composite according to claim 1, comprising the steps of: (S1) doping at least one sulfur in a porous carbon material; (S2) impregnating the result of step (S1) with a transition metal-containing precursor solution, and then removing the solvent; Including, The method for producing a carbon composite, wherein the step (S1) includes a step of heat treating a sulfur-doped precursor and the porous carbon material in a contact state.
19. The method for producing a carbon composite according to claim 18, wherein the heat treatment is carried out at a temperature of 800°C to 1,000°C.
20. The sulfur-doped precursors are dibenzyl disulfide (DBDS), sodium pyrosulfite (Na 2 S 2 O 5 ), sodium pyrosulfate (Na 2 S 2 O 7 ), sodium thiosulfate (Na 2 S 2 O 3 ), thiourea (CH 4 N 2 S), sodium sulfide (Na 2 S), potassium thiocyanate (KSCN), benzyl mercaptan (C 7 H 8 S), benzothiophene (C 8 H 6 S), dibenzothiophene (C 12 H 8 S), or a mixture thereof.
21. The transition metal-containing precursor solution in the step (S2) is An organic solvent; a precursor compound of a non-metallic element; A precursor compound of a transition metal.
22. A positive electrode active material for a lithium-sulfur battery, comprising: A carbon composite material comprising the carbon composite material according to any one of claims 1 to 17 and a sulfur-based compound, The positive electrode active material, wherein the sulfur-based compound is lithium sulfide (Li 2 S), lithium polysulfide (Li 2 S x , 2≦x≦8), a disulfide compound, or a mixture of two or more of these.
23. A positive electrode comprising the positive electrode active material of claim 22.
24. The battery includes a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte solution; 24. A lithium-sulfur battery, wherein the positive electrode is the positive electrode of claim 23.
25. A positive electrode for a lithium-sulfur battery, comprising: A positive electrode active material containing a sulfur-based compound and the carbon composite according to any one of claims 1 to 17, The sulfur-based compound is lithium sulfide (Li 2 S), lithium polysulfide (Li 2 S x , 2≦x≦8), a disulfide compound, or a mixture of two or more of these.
26. The battery includes a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte solution; 26. A lithium-sulfur battery, wherein the positive electrode is the positive electrode of claim 25.
Citation Information
Patent Citations
Catalyst for cathode material for lithium secondary battery and lithium secondary battery including same
JP2022505581A